2020
DOI: 10.1186/s40249-020-00708-0
|View full text |Cite
|
Sign up to set email alerts
|

Transmissibility of COVID-19 in 11 major cities in China and its association with temperature and humidity in Beijing, Shanghai, Guangzhou, and Chengdu

Abstract: Background: The new coronavirus disease COVID-19 began in December 2019 and has spread rapidly by human-to-human transmission. This study evaluated the transmissibility of the infectious disease and analyzed its association with temperature and humidity to study the propagation pattern of COVID-19. Methods: In this study, we revised the reported data in Wuhan based on several assumptions to estimate the actual number of confirmed cases considering that perhaps not all cases could be detected and reported in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…Several researchers around the world have demonstrated an inverse relationship between air temperature and COVID-19 transmissibility. [23][24][25][26][27] Our results also are in agreement with the general understanding that higher ambient temperature can inversely influence COVID-19 transmissibility. 23,27 The study duration mark a period of increasing temperature in the Indian peninsula and our results indicate that, in general, high ambient temperatures were associated with lower R 0 estimates such that unit standard deviation increase in air temperature was associated with a 0.08 lower R 0 (Table 1, final model).On the other hand, we observed that a unit standard deviation increase in wind speed was associated with a 0.08 higher R 0 ( Table 1, (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionsupporting
confidence: 91%
“…Several researchers around the world have demonstrated an inverse relationship between air temperature and COVID-19 transmissibility. [23][24][25][26][27] Our results also are in agreement with the general understanding that higher ambient temperature can inversely influence COVID-19 transmissibility. 23,27 The study duration mark a period of increasing temperature in the Indian peninsula and our results indicate that, in general, high ambient temperatures were associated with lower R 0 estimates such that unit standard deviation increase in air temperature was associated with a 0.08 lower R 0 (Table 1, final model).On the other hand, we observed that a unit standard deviation increase in wind speed was associated with a 0.08 higher R 0 ( Table 1, (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionsupporting
confidence: 91%
“…Daily COVID-19 death counts were positively associated with the diurnal temperature range, but had a negative association with relative humidity from January 20, 2020 to February 29, 2020 in Wuhan [17]. The effects of low temperatures, a mild diurnal temperature range and low humidity was said to increase the spread of COVID-19, conversely, it was said the warmer weather in China from January 20 to March 2020 minimized its spread [18][19][20]. A recent meta-analysis showed that the overall intensity of the COVID-19 epidemic in China reduced slightly following the days with higher temperatures [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers around the world have demonstrated an inverse relationship between air temperature and number of COVID-19 cases ( Demongeot et al, 2020 ; Guo et al, 2020 ; Harmooshi et al, 2020 ; Jahangiri et al, 2020 ; Malki et al, 2020 ; Pramanik et al, 2020 ; Ran et al, 2020 ; Ren et al, 2020 ; Seligmann et al, 2020a ; Steiger et al, 2020 ). Our results are in agreement with the general understanding that higher ambient temperature can inversely influence COVID-19 transmissibility ( Guo et al, 2020 ; Jahangiri et al, 2020 ). Our study duration marks a period of increasing temperature in the Indian peninsula and our results indicate that, in general, high ambient temperatures were associated with lower R 0 estimates such that one standard deviation increase in air temperature was associated with a 0.08 lower R 0 ( Table 3 , final model).…”
Section: Discussionmentioning
confidence: 99%